A methodology to estimate security of supply in electricity generation: results for Germany until 2030 given a high level of intermittent electricity feed-in - Moritz Paulus; Katharina Grave; Dietmar Lindenberger (Institute of Energy Economics at the University of Cologne (EWI), 2011)
In this paper, we develop a methodology for deriving a consistent measure for supply adequacy in the power generation sector. We especially consider the secured generation capacity of intermittent renewable energy sources such as wind. Availability of conventional power plants is estimated through stochastic convolution of unscheduled non-usabilities. We employ our methodology to measure supply security in Germany until 2030. A detailed market analysis of power plants that are currently being built or planned provides support to our analysis for the short term. For the long term, we rely on a large-scale dispatch and investment model of the European power sector to account for the embedding of the German electricity sector in the European market. We analyze two scenarios: one with prolongation of nuclear power plants and one with a nuclear phase-out. Our results show that, even though intermittent renewables only provide very limited secured generation capacity, security of electricity supply in Germany can be assured until 2015. In the long term, the need for backup capacity for renewable energy sources increases as well as the need for electricity imports.
Keywords: C61; L94; Q21; Q40; 330; Supply adequacy; integration of renewable energy sources; power generation; German power sector; secured generation capacity